ROADMAP PENELITIAN PRODI PENDIDIKAN AGAMA ISLAM IAIN PONTIANAK TAHUN 2022-2030 - Rizki Susanto; Arief Adi Purwoko; Weni Ayu Sundari; Rosanti Rosanti (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
The research roadmap is an important element for the sustainability of higher education in the field of research. Demands for harmony between research conducted in tertiary institutions and national policies are the main key in responding to community needs in the educational aspect of globalization. The purpose of this study is to design a research roadmap for the IAIN Pontianak PAI Study Program in 2022–2030. This study uses a qualitative descriptive approach with supporting data in the form of research policies on the 2017–2045 National Research Master Plan document, the 2018–2028 National Religious Research Agenda, and the Research and Community Service Roadmap of IAIN Pontianak, as well as data records of the thesis titles of PAI IAIN Pontianak students from 2018–2021. According to the search results, 1) research by PAI students has accommodated RIRN through character research and out-of-school education; ARKAN on 4 themes and 8 sub-themes; and IAIN Pontianak's research roadmap through research with a local Kebornean pattern; and 2) the research roadmap for the PAI IAIN Pontianak study program is directed at achieving graduate profiles and the integration of PAI knowledge with other disciplines so that research results can be published.